Stochastic Pollution and Environmental Care in an Endogenous Growth Model - Susanne Soretz (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2002)
This paper analyzes the impact of pollution and abatement policy within a stochastic endogenous growth model. The agents have environmental preferences, but they neglect their individual contribution to aggregate abatement. Therefore, environmental care is done by the government and financed via income taxation and government bonds. Equilibrium growth depends on environmental preferences, perception of aggregate capital and risk aversion. Environmental care as well as fiscal policy are analyzed. Due to environmental preferences and partial anticipation of the dependence between aggregate and individual capital, government debt influences equilibrium growth. Hence, income taxation has an additional indirect impact on accumulation through the simultaneous adjustment of portfolio choice. From numerical simulation it can be concluded that the optimal income tax rate decreases with the perception of the influence of individual on aggregate capital. In contrast, the impact of environmental preferences and uncertainty on optimal financing is ambiguous.
Keywords: D8; D9; H2; O1; O4; Q2; 330; pollution; endogenous growth; uncertainty; taxation; Umweltökonomik; Umweltbelastung; Umweltkosten; Einkommensteuerpolitik; Öffentliche Schulden; Neue Wachstumstheorie; Theorie